Analysis of factors causing the occurrence of neonatural asphysia in pariaman hospital - Resty Noflidaputri (Science Midwifery, 2023)
Neonatal asphyxia is a condition in which a newborn does not immediately breathe spontaneously and regularly after birth. Neonatal asphyxia is one of the causes of infant mortality in the world which ranks second. The purpose of this study was to analyze, discuss, and interpret the factors that cause neonatal asphyxia. This study used a qualitative descriptive design with a phenomenological strategy using in-depth interviews, observation, and document review. Informants in this study amounted to 25 people with techniques purposive sampling. Processing uses data reduction, data presentation, drawing conclusions and verification. Data analysis using technical triangulation and source triangulation. The results showed that most of the causes of neonatal asphyxia in Pariaman Hospital were mostly caused by LBW and prematurity, human resources, infrastructure still needed quality improvement, improvement, and additions, especially for cases of severe asphyxia. SPO, RKK, and funds are good enough. In terms of process, there must be a resuscitation team and supervision of the implementation of the SPO. Cases of mild to moderate neonatal asphyxia can be handled properly, but if there are cases of severe asphyxia, a referral needs to be made because of incomplete infrastructure. Pariaman Hospital is not ready to anticipate the occurrence of neonatal asphyxia due to lack of training and quantity of health workers,standbywhen there is a risk of birth asphyxia neonaturum For this, it is hoped that the hospital canupgradeHuman resources, infrastructure, and being able to form a neonatal resuscitation team if a baby is born at risk of neonatal asphyxia.